A Time Efficient Adaptive Gridding Approach and Improved Calibrations in Five-Hole Probe Measurements - Jason Town; Cengiz Camci (International Journal of Rotating Machinery)
Five-Hole Probes (FHP), being a dependable and accurate aerodynamic tool, are an excellent choice for measuring three-dimensional flow fields in turbomachinery. To improve spatial resolution, a subminiature FHP with a diameter of 1.68 mm is employed. High length to diameter ratio of the tubing and manual pitch and yaw calibration cause increased uncertainty. A new FHP calibrator is designed and built to reduce the uncertainty by precise, computer controlled movements and reduced calibration time. The calibrated FHP is then placed downstream of the nozzle guide vane (NGV) assembly of a low-speed, large-scale, axial flow turbine. The cold flow HP turbine stage contains 29 vanes and 36 blades. A fast and computer controllable traversing system is implemented using an adaptive grid method for the refinement of measurements in regions such as vane wake, secondary flows, and boundary layers. The current approach increases the possible number of measurement points in a two-hour period by 160%. Flow structures behind the NGV measurement plane are identified with high spatial resolution and reduced uncertainty. The automated pitch and yaw calibration and the adaptive grid approach introduced in this study are shown to be a highly effective way of measuring complex flow fields in the research turbine.